Porous particles and methods of making same
The porous particles with an open -hole system through the suspension aggregation reaction solve the problem of gastric dissolving and impurities adsorption during the process of protein purification, and achieve efficient and stable protein purification effects.
Patent Information
- Application Number
- CN202380047667.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-05-11
- Filing Date
- 2023-12-21
- Publication Date
- 2025-01-28
AI Technical Summary
The existing hydrophilic agarose resins are prone to stomach soluble during protein purification, resulting in a decrease in purification speed and efficiency, and the non-specific adsorption of impurities affects the purification effect.
The porous particles with an open -hole system are prepared through the suspension aggregate reaction. They use the polymerization monomer, crosslinker, and pores with an oxygen -containing group to increase the surface area and pore rate of the particles to reduce the non -specific adsorption of impurities of impurities. Essence
Improve the efficiency and purification of protein, reduce the non -specific adsorption of impurities, and ensure the stability and high purification ability of the particles.
Smart Images

Figure CN119384314A_ABST
Abstract
Description
Technical Field
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims the benefit of Korean Patent Application No. 10-2023-0013569 filed on February 1, 2023, in the Korean Intellectual Property Office, and Korean Patent Application No. 10-2023-0061331 filed on May 11, 2023, in the Korean Intellectual Property Office, the disclosures of which are incorporated herein by reference in their entirety.
[0003] The present invention relates to porous particles and methods for preparing the same. More specifically, the present invention relates to porous particles for affinity chromatography and methods for preparing the same. Background Art
[0004] As the fields of biopharmaceuticals and regenerative medicine expand, there is an increasing demand for systems that can effectively separate and purify cells, tissues, microorganisms, etc.
[0005] In conventional affinity chromatography techniques, purification resins made of hydrophilic agarose are mainly used, but such resins are swollen by buffer solutions during the purification process and thus cause strength reduction, which leads to deterioration of purification speed and purification efficiency. Therefore, attempts have been made to prepare synthetic polymers with improved strength.
[0006] When using purification resins, nonspecific binding of impurities occurs mainly through hydrophobic interactions. Adsorbed impurities may contaminate purified resin particles and have an adverse effect on the activity of the protein A ligand immobilized on the resin and the binding of the target substance. In addition, if impurities flow out with the purified target substance, the purity of the final product is reduced, and if the impurities are administered to patients, they may induce an immune response.
[0007] Therefore, there is a need to develop technologies regarding particles that can reduce nonspecific adsorption and methods for preparing the same. Summary of the invention
[0008] Technical issues
[0009] It is an object of the present application to provide porous particles having an open pore system.
[0010] Another object of the present application is to provide porous particles with reduced non-specific adsorption.
[0011] Another object of the present application is to provide particles (eg, column resins) for protein purification.
[0012] Yet another object of the present application is to provide porous particles suitable for affinity chromatography.
[0013] Yet another object of the present application is to provide a method for preparing the porous particles as described above.
[0014] The above and other objects of the present application can all be solved by the present application described in detail below.
[0015] Technical Solution
[0016] According to one embodiment of the application, porous particles and preparation methods thereof are provided. The particles can be used as particles (column resins) for protein purification, particularly particles for affinity chromatography. In this article, "porous particles" may refer to particles with holes inside and / or on the surface of each particle. More specifically, porous particles may refer to particles with an open pore system.
[0017] The particles (column resin) used for protein purification are exposed to a solution containing antibody proteins and other cell culture-derived impurities. As a result, impurities are non-specifically adsorbed on the particle surface. In order to ensure the binding between the particles and the target substance and to improve the purity of the final product, the non-specific adsorption of impurities must be reduced. The inventors of the present application experimentally determined that the following preparation method and the particles prepared thereby can reduce such non-specific adsorption, and completed the invention of the present application.
[0018] Specifically, in order for porous particles to have sufficient purification ability in affinity chromatography, the target substance (e.g., IgG) must be able to bind to the protein A ligand as much as possible. In order to provide such binding as much as possible, a large amount of ligands must be fixed to the particles because the specific surface area of the particles is high. In order to increase the specific surface area, the pores of the particles must be large enough, and the number of pores (or porosity) must also be ensured at a high level. This is because, if the pores of the particles are small, when the ligand is fixed, the ligand may not be able to move to the inside of the particles, and when the target substance is purified, the target substance may not be able to move inside. In addition, in order to smoothly carry out purification, the shape of the particles needs to be uniform.
[0019] Furthermore, during the purification process, adsorption between impurity proteins and purification particles occurs mainly through hydrophobic bonds between the impurity proteins and the purification particles, so that when the particles have more hydrophilic groups, the hydrophobic bonds (nonspecific adsorption) can be reduced.
[0020] Taking such viewpoints into consideration, the inventors of the present application conducted extensive studies on materials for preparing porous particles, their contents, reaction conditions, surface characteristics of particles, and the like, and completed the invention of the present application.
[0021] Now, the invention of the present application will be described in more detail.
[0022] In one embodiment related to the present application, the present application relates to a method for preparing porous particles. The porous particles prepared according to the method of the present application may have characteristics suitable for protein purification purposes, in particular for affinity chromatography.
[0023] Specifically, the method comprises mixing a dispersed phase composition (A) with a continuous phase composition (B) in a reactor, and then subjecting the mixture to a suspension polymerization reaction. Wherein, "dispersed phase composition" means a composition that can form a dispersed phase (or droplets) after mixing with a continuous phase composition, and "continuous phase composition" means a composition that can form a continuous phase after mixing with a dispersed phase composition.
[0024] In one embodiment of the present application, the dispersed phase composition comprises a polymerizable monomer (b1) containing an epoxy group, a crosslinking agent (b2) and a pore former (b3). In one embodiment of the present application, in addition to the polymerizable monomer (b1) containing an epoxy group, the crosslinking agent (b2) and the pore former (b3), the dispersed phase composition may also comprise an initiator (b4). In another embodiment, the dispersed phase composition may be a mixture of the above components.
[0025] By suspension polymerization of the dispersed phase composition, a suspension polymerization product comprising units derived from a polymerizable monomer (b1) and a crosslinking agent (b2) can be obtained. More specifically, a suspension polymerization product comprising units derived from a polymerizable monomer (b1) and a crosslinking agent (b2), or a reaction product between a polymerizable monomer (b1) (carried out by an initiator) and a crosslinking agent (b2) can be obtained by suspension polymerization. The suspension polymerization product may be a particle or a particle group including particles, and each individual particle may have the following particle characteristics.
[0026] In an exemplary embodiment, the polymerizable monomer (b1) may be a monomer containing an unsaturated bond between a carbon and an epoxy group (or a glycidyl group). The type of such a polymerizable monomer is not particularly limited, but may be, for example, a (meth)acrylate monomer having an epoxy group, and more specifically, glycidyl (meth)acrylate, 4,5-epoxybutyl (meth)acrylate, or 9,10-epoxystearyl (meth)acrylate may be mentioned. However, the type of polymerizable monomer contained in the dispersed phase composition of the present application is not specified by the monomers listed above.
[0027] The dispersed phase composition further comprises a crosslinking agent (b2). In one embodiment of the present application, a compound containing at least two double bonds between carbons (eg, vinyl groups) that can participate in a crosslinking reaction may be used as a crosslinking agent.
[0028] According to the embodiment of the present application, the cross-linking agent that can be used includes, for example, multifunctional (meth) acrylates, such as ethylene glycol di(meth) acrylate, trimethylolpropane tri(meth) acrylate, pentaerythritol tri(meth) acrylate, dipentaerythritol hexa(meth) acrylate, dipentaerythritol hexamethacrylate or trimethylolpropane trimethacrylate. Alternatively, one or more of the cross-linking agents listed above can be used in combination.
[0029] In an exemplary embodiment, the crosslinking agent compound may be a compound that does not contain a hydrophilic group (e.g., a hydroxyl group). As a result of experimental confirmation, if the crosslinking agent contains a hydrophilic group in addition to the double bond between carbons, the reaction rate of the crosslinking agent may be reduced, which may lead to conditions that make it difficult to form sufficient particle pores.
[0030] The dispersed phase composition also contains a pore former (b3). The pore former does not participate in the polymerization reaction, but is a component that can form pores in the polymerized particles while escaping from the dispersed phase droplets during the suspension polymerization reaction.
[0031] In one embodiment of the present application, the porogen (b3) may be a porogen having a Hansen solubility parameter difference of 1.30 to 4.70 from the epoxy-containing polymerizable monomer (b1), or may include such a porogen. Specifically, the difference in Hansen solubility parameter between the epoxy-containing polymerizable monomer (b1) and the porogen may be 1.40 or more, 1.50 or more, 1.60 or more, 1.70 or more, 1.80 or more, 1.90 or more, 2.00 or more, 2.10 or more, 2.20 or more, 2.30 or more, 2.40 or more, 2.50 or more, 2.60 or more, 2.70 or more, 2.80 or more, 2.90 or more, 3.00 or more, 3.10 or more, 3.20 or more, 3.30 or more, 3.40 or more, 3.50 or more, 3.60 or more, 3.70 or more, 3.80 or more, 3.90 or more, or 4.00 or more. In addition, its upper limit may be, for example, 4.60 or less, 4.50 or less, 4.40 or less, 4.30 or less, 4.20 or less, 4.10 or less, 4.00 or less, 3.90 or less, 3.80 or less, 3.70 or less, 3.60 or less, 3.50 or less, 3.40 or less, 3.30 or less, 3.20 or less, 3.10 or less, or 3.00 or less. As a result of experimental confirmation, if the difference in the Hansen solubility parameter is satisfied, a particle having a porous structure allowing a target substance to reach the center of the particle while having sufficiently large surface pores to allow the target substance to flow into the interior of the particle can be provided.
[0032] In an exemplary embodiment, non-aromatic materials can be used as pore formers. For example, the pore former can be or include a material (pore former) based on acetate. In one embodiment, the pore former component can be selected from at least one of butyl acetate, isobutyl acetate, amyl acetate, isoamyl acetate, hexyl acetate, isohexyl acetate and heptyl acetate. When using a pore former based on acetate that satisfies the value associated with the above-mentioned solubility parameter, it is beneficial to ensure that the particles have sufficient purification capabilities in affinity chromatography applications. Specifically, when using another type of pore former (for example, an aromatic pore former, such as toluene or mesitylene) to replace the above-mentioned pore former based on acetate, it is experimentally determined that the deviation of the degree of occurrence of broken particles is large. That is, when preparing particles as in the present application, the ratio of broken particles can be greatly reduced (stably forming particles without cracks), and particles with sufficiently large holes can be provided, so this is conducive to reducing nonspecific adsorption.
[0033] In one embodiment of the present application, the dispersed phase composition may also include an initiator (b4). The type of initiator is not particularly limited, as long as it does not hinder the particle characteristics required in the present application. For example, an initiator such as an organic peroxide initiator or an azo initiator may be used. Specifically, compounds such as benzoyl peroxide, di-tert-amyl peroxide, tert-butyl perbenzoate, 2,5-dimethyl-2,5-di-(tert-butyl peroxy) hexane, 2,5-dimethyl-2,5-di-(tert-butyl peroxy) hexine-3, dicumyl peroxide, lauryl peroxide, 2,2'-azobis(2,4-dimethylvaleronitrile) and mixtures thereof may be used, but are not limited thereto.
[0034] In one embodiment of the present application, based on 100 parts by weight of the cross-linking agent (b2), the dispersed phase composition may include 50 parts by weight or more of the polymerizable monomer (b1). For example, based on 100 parts by weight of the cross-linking agent (b2), the dispersed phase composition may include the polymerizable monomer (b1) in the following amounts: 60 parts by weight or more, 70 parts by weight or more, 80 parts by weight or more, 90 parts by weight or more, 100 parts by weight or more, 110 parts by weight or more, 120 parts by weight or more, 130 parts by weight or more, 140 parts by weight or more, 150 parts by weight or more, 160 parts by weight or more, 170 parts by weight or more, 180 parts by weight or more, 190 parts by weight or more, or 200 parts by weight or more. The upper limit of the content of the polymerizable monomer (b1) in the dispersed phase composition can be, for example, 400 parts by weight or less, 350 parts by weight or less, 300 parts by weight or less, 250 parts by weight or less, 200 parts by weight or less, 150 parts by weight or less, or 100 parts by weight or less. In addition, in a specific embodiment of the present application, based on 100 parts by weight of the cross-linking agent (b2), the polymerizable monomer (b1) can be included in an amount of 100 parts by weight or more, 150 parts by weight or more, or 200 parts by weight or more. When the above content is met, an emulsion is stably formed, particle breakage during polymerization is greatly suppressed, and an appropriate level of particle strength can be ensured without making the pore size of the final particles too large or too small. In particular, when the content of components (b1) and (b2) meets the above range, the proportion of broken particles can be reduced (particles without cracks are stably formed), and particles with sufficiently large pores can be provided, so this is conducive to reducing nonspecific adsorption.
[0035] In one embodiment of the present application, based on 100% by weight of the total content of polymerizable monomer (b1), crosslinking agent (b2) and pore former (b3), the dispersed phase composition may contain pore former (b3) in an amount of 45% by weight or more. For example, based on 100% by weight of the total content, the content of pore former (b3) (which may be, for example, a pore former based on acetate) may be 50% by weight or more, 55% by weight or more, or 60% by weight or more. In addition, the upper limit of the content may be, for example, 70% by weight or less, 65% by weight or less, 60% by weight or less, or 55% by weight or less. If the above content is met, it is beneficial to stably form an emulsion and ensure the particle characteristics (for example, less particle rupture and high spheroidization rate) suitable for the intended use. In particular, when the content of components (b1) and (b2) meets the above range, the proportion of broken particles can be reduced (particles without cracks are stably formed), and particles with sufficiently large pores can be provided, so this is beneficial to reduce nonspecific adsorption.
[0036] The content of initiator (b4) is not particularly limited.Initiator can be used with appropriate amount on the level that does not hinder to ensure the desired particle characteristics.For example, relative to the gross weight of 100 weight parts of polymerizable monomer and crosslinking agent, dispersed phase composition can be with 0.1 weight part or more, specifically 0.2 weight part or more, 0.3 weight part or more, 0.4 weight part or more, 0.5 weight part or more, 0.6 weight part or more, 0.7 weight part or more, 0.8 weight part or more, 0.9 weight part or more or 1.0 weight part or more amount comprises initiator.In addition, the upper limit of the content of initiator can be for example 5.0 weight parts or less, specifically, 4.5 weight parts or less, 4.0 weight parts or less, 3.5 weight parts or less, 3.0 weight parts or less, 2.5 weight parts or less, 2.0 weight parts or less, 1.5 weight parts or less or 1.0 weight part or less.
[0037] In an exemplary embodiment, the continuous phase composition (A) may include water and a polymeric surfactant.
[0038] Although not particularly limited, the water may be distilled water or deionized water (DIW).
[0039] In an exemplary embodiment, the continuous phase composition may be a mixture of water and a polymeric surfactant. That is, the continuous phase composition may consist of only water and a polymeric surfactant.
[0040] In the embodiments of the present application, the polymer surfactant may have a weight average molecular weight (Mw) within a predetermined range and / or a degree of hydration (hydrolysis degree) within a predetermined range.
[0041] In an exemplary embodiment, the weight average molecular weight of the polymer surfactant can be 60,000 or greater. Specifically, the lower limit of the weight average molecular weight can be, for example, 65,000 or greater, 70,000 or greater, 80,000 or greater, 85,000 or greater, 90,000 or greater, 95,000 or greater, 100,000 or greater, 105,000 or greater, 110,000 or greater, 115,000 or greater, 120,000 or greater, 125,000 or greater, 130,000 or greater, 135,000 or greater, 140,000 or greater. In addition, its upper limit can be 200,000 or less. Specifically, the upper limit of the weight average molecular weight can be, for example, 190,000 or less, 185,000 or less, 180,000 or less, 175,000 or less, 170,000 or less, 165,000 or less, 160,000 or less, 155,000 or less, 150,000 or less, 145,000 or less, 140,000 or less, 135,000 or less, 130,000 or less, 125,000 or less, 120,000 or less, 115,000 or less, or 110,000 or less. The weight average molecular weight can be measured using GPC.
[0042] In an exemplary embodiment, the degree of hydration of the polymer surfactant can be in the range of 80% to 99%. More specifically, the lower limit of the degree of hydration can be, for example, 81% or higher, 82% or higher, 83% or higher, 84% or higher, or 85% or higher, and its upper limit can be, for example, 98% or lower, 97% or lower, 96% or lower, 95% or lower, 94% or lower, 93% or lower, 92% or lower, 91% or lower, or 90% or lower. For example, polyvinyl alcohol can be used as a surfactant with the above degree of hydration. The degree of hydration can be measured using 1H-NMR.
[0043] Examples of polymeric surfactants that may be used include poly(vinyl alcohol) (PVA) or polyvinyl pyrrolidone.
[0044] In an exemplary embodiment, in the continuous phase composition, the concentration of the polymer surfactant can be 1.0% or more. For example, when a continuous phase composition of a mixture of water and a polymer surfactant is used, the content of the polymer surfactant can be 1.0% by weight or more based on the gross weight (100% by weight) of the continuous phase composition. Specifically, the lower limit of the concentration of the polymer surfactant in the continuous phase composition (A) can be 1.5% by weight or more, 2.0% by weight or more, 2.5% by weight or more, 3.0% by weight or more, or 3.5% by weight or more, and the upper limit of the concentration of the polymer surfactant can be less than 4.0%, specifically, for example, 3.5% or less, 3.0% or less, 2.5% or less, 2.0% or less, or 1.5% or less. When a polymer surfactant satisfying the above concentration is used, when the continuous phase and the powder phase are mixed, uniform and stable droplets can be formed, which is conducive to obtaining the final particle shape expected by the present application.
[0045] In an exemplary embodiment, the weight ratio of the dispersed phase composition to the continuous phase composition (weight ratio of the dispersed phase composition:weight ratio of the continuous phase composition) can be in the range of 1:2 to 1:15, or in the range of 1:4 to 1:12, or in the range of 1:6 to 1:10.
[0046] According to the preparation method of the present application, suspension polymerization can be performed under conditions that do not hinder the securing of particle characteristics. For example, the suspension polymerization reaction can be performed at a temperature of 100° C. or lower, more specifically at a temperature of 40° C. to 95° C. In addition, during the polymerization reaction at the above temperature, stirring can be performed at a speed of 600 rpm to 1,000 rpm.
[0047] In an exemplary embodiment, the method may also include a washing step after the suspension polymerization reaction is completed. By this washing, impurities unrelated to the particles of the suspension polymerization product can be removed. The washing method is not particularly limited, and any known washing method can be used. For example, washing can be performed by adding the suspension polymerization product to a washing solution containing alcohol (e.g., an alcohol containing ethanol) and / or high temperature (e.g., 40°C to 60°C) water (e.g., distilled water), and then stirring. Although not particularly limited, the washing can be repeated, for example, twice or more times.
[0048] In an exemplary embodiment, the method may further include a drying step after washing. Solvent residues, etc. may be removed by drying. The drying method is not particularly limited, and any known drying method may be used. For example, an oven may be used or drying may be performed at room temperature. In addition, although not particularly limited, drying may be performed in a vacuum.
[0049] In an exemplary embodiment, the method may further include centrifuging, washing and drying the suspension polymerization product after the suspension polymerization reaction is completed. The details about washing and drying are the same as those described above.
[0050] The suspension polymerization product, ie, particles, prepared according to the above methods including suspension polymerization may have properties suitable for protein purification or separation applications.
[0051] In an exemplary embodiment, the size of the particles prepared according to the method of the present application may be in the range of 30 μm to 70 μm. Here, the particle size refers to the particle size (D) measured using a PSA (particle size analysis) device. 50 ). In addition, D 50 It means the particle size corresponding to 50% cumulative volume in the particle size distribution. Specifically, the particles prepared according to the present application may have a lower limit size of 35 μm or more, 40 μm or more, or 45 μm or more, and an upper limit size of 65 μm or less, 60 μm or less, 55 μm or less, 50 μm or less, or 45 μm or less. In the case of exceeding the above particle range, the number of particles that can be filled in the purification column is reduced, the content of the ligand attached to the particle surface is reduced, and the final purification efficiency may be reduced. In addition, when the particle size is smaller than the above particle size, the density of the particles (filling beads) filled in the purification column becomes too large, making it difficult for the solution to be purified to escape, so this may reduce the purification efficiency.
[0052] In an exemplary embodiment, the method of the present application can provide a particle group with a low percentage of broken particles. For example, the proportion of the number of broken particles can be 20% or less, 15% or less, 10% or less, or 5% or less of the total particles prepared. That is, according to the present application, particles with a stable shape are provided. If the proportion of broken particles is high, it can be seen that the preparation efficiency is low. In addition, when the particles are used for protein purification, the purification efficiency may be reduced due to the broken particles blocking the channel through which the solution flows, and the product purity may be reduced due to the broken particles escaping through the column outlet.
[0053] In an exemplary embodiment, the particles can exhibit a high spheroidization rate. For example, the particle size (D 50 The spheroidization rate of the ratio of the length (L) of the particles having the longest dimension length (L) in the total particles prepared can be 80% or more, 85% or more, or 90% or more. That is, according to the present application, uniform particles with high spheroidization are provided. If the spheroidization rate is low, the purification efficiency may be reduced because the particles are not fully packed in the column.
[0054] In an exemplary embodiment, when the pore size is measured using mercury intrusion, the pore size of the particle can be 30nm or larger. Mercury intrusion is a method of measuring the pore size by converting the amount of mercury introduced from the surface of the particle to the inside by pressure. According to the embodiment of the present application, the measurement data related to mercury intrusion can be represented by a histogram, and the size of the particle pore can be calculated by the measurement result of the total intrusion volume under the maximum mercury intrusion pressure and the ratio of the total pore area (wherein, the size of the particle pore can be considered to be the average size, and the average value can mean the arithmetic mean). If the pore of the particle is too small, only impurities with a smaller size relative to the target protein will flow into the interior of the particle and be adsorbed inside the particle, which may cause the purification efficiency to decrease due to the increase of nonspecific adsorption. For example, the pore size of the particle can be 35nm or larger, 40nm or larger, 45nm or larger, 50nm or larger, 55nm or larger, or 60nm or larger. In addition, the upper limit of the average pore size of the particle can be 500nm or less. When the average pore size of the particles is too large, the residence time of impurities in the interparticle spaces smaller than the particle pores may increase, and the purification efficiency may decrease due to the increase in nonspecific adsorption. In addition, due to the decrease in the specific surface area inside the particles, the content of the attached ligand may decrease, so this may reduce the purification efficiency. For example, the pore size of the particles may be 400 nm or less, 300 nm or less, 200 nm or less, or 100 nm or less.
[0055] In an exemplary embodiment, the average surface pore size of the particles may be in the range of 110 nm to 240 nm. In one embodiment of the present application, the average surface pore size is related to the openness of the particle surface and may mean the (arithmetic) average value calculated after measuring 20 or more pore sizes (wherein the pore size means the length of the largest dimension in the pore shape) on the SEM image of the particle surface. It is not possible to determine the openness of the particle surface only from the particle pore size determined by mercury intrusion. Taking into account the flow of the target substance or fluid through the particles, the specific surface area of the particles, the mechanical strength of the particles, etc., the average surface pore size can be, for example, 120nm or more, 130nm or more, 140nm or more, 150nm or more, 160nm or more, 170nm or more, 180nm or more, 190nm or more, or 200nm or more, and its upper limit can be, for example, 230nm or less, 220nm or less, 210nm or less, 200nm or less, 190nm or less, 180nm or less, 170nm or less, 160nm or less, or 140nm or less.
[0056] In an exemplary embodiment, the porosity of the particles can be in the range of 15% to 40%. Specifically, the porosity of the particles can be, for example, 16% or more, 17% or more, 18% or more, 19% or more, 20% or more, 21% or more, 22% or more, 23% or more, 24% or more, 25% or more, and 39% or less, 38% or less, 37% or less, 36% or less, 35% or less, 34% or less, 33% or less, 32% or less, 31% or less, or 30% or less. If the porosity is less than the above range, it is difficult to expect high purification efficiency due to the low specific surface area of the particles. If the porosity exceeds the above range, the mechanical strength may deteriorate.
[0057] In one embodiment of the present application, the method further comprises a predetermined surface treatment step for the suspension polymerization product. Specifically, the method further comprises a step of making the surface of the suspension polymerization product hydrophilic by passivating epoxy groups.
[0058] The particles obtained by the above suspension polymerization have epoxy groups derived from the polymerizable monomer containing epoxy groups. In the present application, an epoxy passivator (e.g., a compound having an epoxy reactive group and a hydrophilic group different from the epoxy reactive group) is reacted with the particles formed by the suspension polymerization to passivate the epoxy groups on the particle surface and introduce hydrophilic groups to the surface of the particles. By introducing hydrophilic groups through epoxy passivation, nonspecific adsorption caused by hydrophobic bonds between impurity proteins and purified particles can be reduced.
[0059] As described above, in one embodiment of the present application, at least 50 parts by weight of the polymerizable monomer (b1) containing an epoxy group is used relative to 100 parts by weight of the crosslinking agent (b2), so that the particles that are the suspension polymerization product have a sufficient amount of epoxy groups on their surface. Since a sufficient amount of epoxy groups on the particle surface is ensured, when the epoxy deactivator and the particles are reacted with each other, the particle surface can be sufficiently hydrophilized due to epoxy deactivation.
[0060] Hydrophilization can be carried out by reacting an epoxy passivating agent having an epoxy reactive group and a hydrophilic group different from the epoxy reactive group with a suspension polymerization product having an epoxy group. For example, the above-mentioned epoxy passivation can be achieved by injecting the prepared particles into an epoxy passivating agent or a solution containing it. The solvent used at this time is not particularly limited. In addition, the reaction for making the surface hydrophilic can be carried out, for example, in the range of 30°C to 50°C for 10 hours to 30 hours.
[0061] In an exemplary embodiment, the epoxy passivating agent may be a compound having an epoxy reactive group and a hydrophilic group different from the epoxy reactive group. The epoxy reactive group may be, for example, a thiol group or an amine group, and the hydrophilic group different from the epoxy reactive group may be, for example, a hydroxyl group.
[0062] For example, the passivator may include at least one selected from 1-thioglycerol, ethanolamine and 2-mercaptoethanol. For example, when 1-thioglycerol is used as the passivator, the passivation of the epoxy group occurs by epoxy-thiol reaction, and when ethanolamine is used as the passivator, the passivation of the epoxy group occurs by epoxy-amine reaction, wherein the former case is more favorable in terms of reaction efficiency. Therefore, it is preferred to use an epoxy passivator such as 1-thioglycerol containing a thiol group as an epoxy reactive group and a hydroxyl group as a hydrophilic group different from the epoxy group.
[0063] In one embodiment of the present application, such a method can provide porous particles exhibiting a low nonspecific adsorption rate, the method comprising: mixing a continuous phase composition (A) and a dispersed phase composition (B), and then subjecting the mixture to a suspension polymerization reaction to prepare a suspension polymerization product comprising units derived from a polymerizable monomer (b1) and a crosslinking agent (b2); and making the surface of the suspension polymerization product hydrophilic by epoxy passivation. For example, the method can provide porous particles having a nonspecific adsorption rate of 1.5% or less for BSA (bovine serum albumin). Specifically, the particles prepared according to the above method can satisfy a nonspecific adsorption rate of 1.0% or less for BSA (bovine serum albumin), more specifically, 0.5% or less, 0.45% or less, 0.4% or less, 0.35% or less, 0.3% or less, 0.25% or less, 0.2% or less, 0.15% or less, 0.1% or less, 0.05% or less, or 0.01% or less. The nonspecific adsorption rate is measured for a mixture containing porous particles, BSA and water, and is calculated as the ratio of the content (weight) of BSA adsorbed on the porous particles to the content (weight) of the total BSA added to the mixture. According to one embodiment of the present application, the porous particles and BSA in the mixture for measuring the nonspecific adsorption rate can be included in a weight ratio of 1 to 3 porous particles: 1 BSA.
[0064] In an exemplary embodiment, the above method can provide particles that meet a predetermined hydrophilic group content. Specifically, the method can provide particles that meet a hydrophilic group content (μmol / g) of 500μmol / g or higher, specifically 1000μmol / g or higher per particle unit weight. Wherein, the hydrophilic group content (μmol / g) per particle unit weight can be calculated by multiplying the epoxy content (μmol / g) of the suspension polymerization product obtained by suspension polymerization before the surface hydrophilization treatment by the number of hydrophilic groups in the epoxy passivator. In addition, the epoxy content (μmol / g) of the suspension polymerization product obtained by suspension polymerization can be calculated by titrating a predetermined weight of particles using 0.1MNaOH to calculate the epoxy content (μmol), and dividing it by the weight of the particles. More specifically, it can be calculated according to the method described in the following experiment. For example, the hydrophilic group (e.g., hydroxyl) content (μmol / g) of the particles provided according to the above method can be 1500 μmol / g or more, 2000 μmol / g or more, 2500 μmol / g or more, 3000 μmol / g or more, 3500 μmol / g or more, 4000 μmol / g or more, or 4500 μmol / g or more. In addition, the upper limit of the hydrophilic group content (μmol / g) of the particles can be, for example, 5000 μmol / g or less, specifically 4500 μmol / g or less, 4000 μmol / g or less, 3500 μmol / g or less, or 3000 μmol / g or less.
[0065] By treating with an epoxy passivating agent as described above, particles having hydrophilic groups within the above range can provide excellent purification efficiency. Specifically, during the purification process, adsorption between impurity proteins and purified particles occurs mainly through hydrophobic bonds between impurity proteins and purified particles. Therefore, when particles have more hydrophilic groups at an appropriate level, hydrophobic bonds (non-specific adsorption) can be reduced. This trend is also confirmed in the following examples.
[0066] In an exemplary embodiment, as a result of epoxy passivation and hydrophilic treatment as described above, the method can provide porous particles in which the content of epoxy groups on the surface is adjusted to a predetermined level or lower. Specifically, the epoxy content (μmol) of the epoxy-passivated particles per unit weight (g) can be 50μmol / g or lower. The epoxy content (μmol / g) can be calculated by titrating a predetermined weight of particles using 0.1M NaOH to calculate the epoxy content (μmol) and dividing it by the weight of the particles. More specifically, it can be calculated according to the method described in the following experiment. In this article, the epoxy content (μmol / g) can be calculated by titrating a predetermined weight of particles using 0.1M NaOH to calculate the epoxy content (μmol) and dividing it by the weight of the particles. More specifically, it can be calculated according to the method described in the experiment described later. Specifically, the epoxy content of the epoxy-passivated particles can be, for example, 45 μmol / g or less, 40 μmol / g or less, 35 μmol / g or less, 30 μmol / g or less, 25 μmol / g or less, 20 μmol / g or less, 15 μmol / g or less, 10 μmol / g or less, or 5.0 μmol / g or less. The epoxy groups of the particles of the present application are derived from the polymerizable material used for particle formation, i.e., polymerizable monomers with epoxy groups. However, assuming that the particles are actually used to purify the target substance, if too many epoxy groups are retained on the particle surface, these epoxy groups may also react with or combine with other substances (e.g., impurities) other than the target substance, so this may reduce the purification efficiency. Taking this into account, particles with passivated epoxy groups are used in the present application. In addition, the lower limit of the epoxy content (μmol) of the epoxy-passivated particles per unit weight may be 1 μmol / g or more, 5 μmol / g or more, 10 μmol / g or more, 15 μmol / g or more, 20 μmol / g or more, 25 μmol / g or more, 30 μmol / g or more, 35 μmol / g or more, or 40 μmol / g or more. For reference, if the epoxy content on the surface of the particles before passivation is too small, the surface hydrophilization treatment by epoxy passivation may not be fully performed. Therefore, when the particles are used as actual column resins, they may not be able to fully bind to substances that must be bound to the particles (e.g., recombinant protein A), and therefore, a sufficient amount of the epoxy-containing polymerizable monomer as described above must be used.
[0067] Although not particularly limited, after the epoxy passivation and hydrophilization treatment, the particles may be washed and / or dried. Washing and drying may be performed in the same manner as described above.
[0068] In one embodiment related to the present application, the present application relates to porous particles. The porous particles can be prepared by the above method, for example, can be used as column resins for protein purification or separation.
[0069] In one embodiment of the present application, the particles include polymerized units derived from a polymerizable monomer having an epoxy group and a crosslinking agent. The types and characteristics of the polymerizable monomer having an epoxy group and the crosslinking agent are the same as described above.
[0070] In an exemplary embodiment, the polymerizable monomer can be a monomer comprising a carbon-carbon unsaturated bond and an epoxy group (or glycidyl group). The type of such a polymerizable monomer is not particularly limited. For example, the polymerizable monomer can include a (meth) acrylate monomer with an epoxy group, more specifically, (meth) glycidyl acrylate, (meth) acrylate 4,5-epoxybutyl ester or (meth) acrylate 9,10-epoxy stearyl ester. However, the type of the polymerizable monomer included in the dispersed phase composition of the present application is not specified to be these monomers.
[0071] In an exemplary embodiment, a multifunctional (meth) acrylate can be used as a crosslinking agent. Specifically, a multifunctional (meth) acrylate such as ethylene glycol di(meth) acrylate, trimethylolpropane tri(meth) acrylate, pentaerythritol tri(meth) acrylate, dipentaerythritol hexa(meth) acrylate, dipentaerythritol hexamethacrylate or trimethylolpropane trimethacrylate can be used as a crosslinking agent. Alternatively, one or more of the crosslinking agents listed above can be used in combination. However, the crosslinking agent is not limited to the materials listed above.
[0072] In addition, the particles of the present application may also contain materials derived from the above-mentioned preparation method.
[0073] In one exemplary embodiment, the particle size (D 50 ) may be in the range of 30 μm to 70 μm. Since the descriptions thereof are the same as those set forth above, no further discussion on this issue will be provided.
[0074] In an exemplary embodiment, the ratio of the number of broken particles of the porous particles to the total particles may be 20% or less.Since the descriptions thereof are the same as those set forth above, further discussion on this issue will not be provided.
[0075] In an exemplary embodiment, the porous particles may satisfy a spheroidization rate of 80% or more.Since the descriptions thereof are the same as those set forth above, further discussion on this issue will not be provided.
[0076] In an exemplary embodiment, the pore size of the porous particles may be 30 nm or more.Since the descriptions thereof are the same as those set forth above, further discussion on this issue will not be provided.
[0077] In an exemplary embodiment, the surface pore size of the porous particles may be in the range of 110 nm to 240 nm.Since the descriptions thereof are the same as those set forth above, further discussion on this issue will not be provided.
[0078] In an exemplary embodiment, the porosity of the porous particles may be in the range of 15% to 40%.Since the descriptions thereof are the same as those set forth above, further discussion on this issue will not be provided.
[0079] In an exemplary embodiment, the particles may be hydrophilically treated, ie, surface treated with an epoxy passivating agent having epoxy reactive groups and hydrophilic groups different from the epoxy reactive groups.
[0080] Epoxy passivation and hydrophilic treatment of particles may mean that the particles have been surface treated with an epoxy passivating agent having epoxy reactive groups and hydrophilic groups different from the epoxy reactive groups. For details of such surface treatment, reference is made to those set forth above.
[0081] In an exemplary embodiment, the porous particles may be particles satisfying a nonspecific adsorption rate of BSA (bovine serum albumin) of 1.5% or less. Since the descriptions thereof are the same as those set forth above, further discussion of this issue will not be provided.
[0082] In an exemplary embodiment, as a result of the epoxy passivation and hydrophilic treatment as described above, the porous particles can meet a predetermined hydrophilic group content. Specifically, the porous particles can meet a hydrophilic group content (μmol / g) of 500 μmol / g or more per unit weight of the epoxy passivated particles, specifically, 1000 μmol / g or more. Since the description thereof is the same as that set forth above, further discussion of this issue will not be provided.
[0083] In an exemplary embodiment, as a result of epoxy passivation and hydrophilic treatment as described above, the porous particles may satisfy a predetermined epoxy content. Specifically, the epoxy content (μmol) of the epoxy-passivated particles per unit weight (g) of the porous particles may be 50 μmol / g or less. Since the description thereof is the same as that set forth above, further discussion of this issue will not be provided.
[0084] Beneficial Effects
[0085] According to one embodiment of the present application, when used for protein purification particles (column resin), particles capable of improving nonspecific adsorption of impurities to particles are provided. Therefore, the binding capacity of antibody protein to particles can be sufficient, and the high purity of the final product can be ensured. BRIEF DESCRIPTION OF THE DRAWINGS
[0086] Figures 1 to 7 is an image of the surface of the particles (base resin) prepared in the examples and comparative examples. Specifically, Figures 1 to 3 are images of the surfaces of the particles (base resin) of Examples 1 to 3 taken using a SEM device, and Figures 4 to 7 These are images of the surfaces of particles (base resin) of Comparative Examples 5 to 7 and Comparative Example 11, respectively, taken using an SEM device. In each figure, a white bar represents a size of 100 nm, and black portions observed in the particles are pores.
[0087] Comparing the figures of the embodiment and the comparative example, the black part, i.e., the hole, is more obvious in the image of the embodiment than in the image of the comparative example. This means that the pores or surface pores of the particles of the embodiment are larger and more numerous than the pores or surface pores of the particles of the comparative example. This means that in the case of the comparative examples (e.g., comparative examples 5 to 7), the pore size measured by the MIP of the particles is at a level of 10nm to 11nm, while in the case of the embodiments (e.g., embodiments 1 to 2), the pore size measured by the MIP of the particles is consistent with the following experimental results (see Tables 5 to 6), which show that the pore size is at a level of 35nm to 40nm. In addition, looking at the experimental results in Tables 5 to 6, it is determined that the embodiments (120nm to 160nm level) and the comparative examples (105nm or less level. In particular, Comparative Example 11 is determined to be 45nm) show a significant difference in average surface pore size. DETAILED DESCRIPTION
[0088] Hereinafter, the functions and effects of the present invention will be described in more detail with reference to specific embodiments. However, this is only for illustrative purposes and is not intended to limit the scope of the present invention in any way.
[0089] Examples and Comparative Examples
[0090] The particle forming components, their contents and process conditions are listed in the following table, and the conditions for preparing each particle in the Examples and Comparative Examples are as follows. If there is no specific explanation about the temperature, the temperature at which the preparation process (or each preparation step) is carried out or the temperature at which the properties of the prepared particles are calculated or measured is room temperature (a temperature without lowering or heating the temperature, which refers to a temperature in the range of about 15°C to 30°C).
[0091] Preparation of dispersed phase
[0092] After the polymerizable monomer (M), the crosslinking agent (C) and the pore former (P) are stirred, BPO (about 1.25 parts by weight relative to 100 parts by weight of the total mass of the polymerizable monomer and the crosslinking agent) is further added as a thermal initiator and stirred at room temperature for about 5 minutes to prepare a dispersed phase.
[0093] *GMA: Glycidyl Methacrylate
[0094] *EGDMA: Ethylene glycol dimethacrylate
[0095] *TMPTMA: Trimethylolpropane trimethacrylate
[0096] Preparation of continuous phase
[0097] PVA (weight average molecular weight (Mw) of 85,000 to 124,000, and hydrolysis rate of 87% to 89%) was dissolved in distilled water at a concentration of 2 wt % to prepare a continuous phase.
[0098] Preparation of particles by suspension polymerization (base resin)
[0099] 720 g of the continuous phase was added to the reactor, and 90 g of the dispersed phase was added, and the mixture was stirred at about 800 rpm at room temperature until a uniform dispersion was formed. Subsequently, the reactor temperature was increased, and polymerization was carried out for about 6 hours at a temperature of about 80° C., about 800 rpm and nitrogen purge conditions.
[0100] Get particles
[0101] The polymerized particles were recovered, washed twice with distilled water at 50° C., and washed five times with ethanol. Subsequently, they were dried in an oven at about 80° C. to obtain particles.
[0102] [Table 1]
[0103] Preparation conditions of the particles (base resin) of Examples 1 to 4
[0104]
[0105] [Table 2]
[0106] Preparation conditions of the pellets (base resin) of Comparative Examples 1 to 4
[0107]
[0108] [Table 3]
[0109] Preparation conditions of the pellets (base resin) of Comparative Examples 5 to 8
[0110]
[0111] [Table 4]
[0112] Preparation conditions of the pellets (base resin) of Comparative Examples 9 to 12
[0113]
[0114] Evaluation 1: Evaluation of base resin properties
[0115] The particles prepared in Examples and Comparative Examples were evaluated according to the following contents.
[0116] 1. Particle (base resin) size
[0117] The prepared particles were dried, the dried particles were dispersed in ethanol at a level of about 10%, and then the particle size (D 50 ). At this time, D 50 It means the particle size corresponding to 50% cumulative volume in a particle size distribution.
[0118] 2. Spheroidization rate of particles (base resin) (%)
[0119] The spheroidization rate was determined by determining the length of the longest dimension (L) in the prepared particles by SEM and calculating the particle size (D 50 ) and the percentage ratio (D 50 / L).
[0120] 3. Particle (base resin) breakage rate (%)
[0121] The particle breakage rate was determined by determining the number of particles having defects on the surface or being broken without maintaining their spherical shape among the prepared particles by SEM, and calculating the percentage rate of the number of particles maintaining the spherical shape relative to the total particles.
[0122] 4. The shape of the particles (base resin) pores
[0123] The pores formed on the surface and inside of the dried particles were observed using a SEM (JEOL JSM7610F-Plus) apparatus.
[0124] 5. Particle (base resin) pore size and particle porosity
[0125] The pore size of the particles was measured using mercury intrusion porosimetry (MIP) (Autopore V9600, micromeritics).
[0126] 6. Surface hole size
[0127] Determine 20 or more pore sizes (wherein pore size means the length of the largest dimension in the pore shape) on the SEM image of the particle surface and calculate the arithmetic mean. Through the calculated surface pore size, the openness of the particle surface can be indirectly determined (which cannot be determined by MIP).
[0128] [Table 5]
[0129] Characteristics of Pellets (Base Resin) of Examples
[0130]
[0131] [Table 6]
[0132] Characteristics of the pellets (base resin) of the comparative example
[0133]
[0134] * In the case of Comparative Examples 8 to 9 and Comparative Example 12, the breakage rate of the particles was high, and thus evaluation on the properties of the particles could not be performed.
[0135] Evaluation 2: Evaluation of nonspecific adsorption rate
[0136] The particles prepared in Examples and Comparative Examples were processed according to the following contents, and the relevant contents were evaluated.
[0137] 1. Epoxy content of particles (base resin), SBC and nonspecific adsorption rate
[0138] (1) Analysis of the epoxy group content (μmol / g) of the pellets (base resin)
[0139] 1) 0.1 g of particles (deionized water was used as a control) were mixed with 1 mL of HCl / acetone solution (1 / 40 (v / v)) and sonicated for 4 minutes (UCP-02 from Jeiotech).
[0140] 2) An indicator solution (0.1% cresol red and 0.1% thymol blue mixed in a volume ratio of 1:3 and adjusted to pH 7.0) was added to the mixed solution of item 1).
[0141] 3) Titrate with 0.1 M NaOH until the color of the solution turns blue-purple.
[0142] 4) Calculate the epoxy content using the following equation.
[0143] [Equation] Epoxy content (mmol)
[0144] =[V0(ml)-V(ml)]×CNaOH(mol / L)
[0145] In the above equation,
[0146] V0: Amount of NaOH added to the control sample using deionized water instead of pellets (mL)
[0147] V: The amount of NaOH added to the experimental group samples containing epoxy groups (mL)
[0148] CNaOH: NaOH concentration used for titration
[0149] 5) Divide the calculated epoxy content by the weight of the particles (0.1 g was used previously in item 1) and determine the epoxy content per weight of the particles (base resin).
[0150] (2) Measurement of SBC (static binding capacity, mg / mL) (reference: Ind. Eng. Chem. Res. 2013, 52, 26, 8800-8811, Biochemical Engineering Journal 145 (2019) 53-61)
[0151] 1) Prepare 50 μL of base resin slurry and thaw the antibody solution (IgG from human serum, 5 mg / mL PBS, pH 7.4), then add 1x PBS to prepare a 3 mg / mL antibody solution.
[0152] 2) After mixing the resin slurry and the antibody solution, IgG was allowed to bind to the resin using a mixer at room temperature for 1 hour.
[0153] 3) After allowing the resin to settle, remove the supernatant (or store if desired) and wash by injecting 5 mL of 1x PBS.
[0154] 4) After the resin was precipitated, the wash solution was removed (or stored as needed), and 500 μL of 100 mM glycine-HCl (pH 2.5) elution solution was injected to elute the IgG.
[0155] 5) After the resin was precipitated, the eluate was collected and stored at 4°C.
[0156] 6) Use UV-vis (8453 UV-visible spectrophotometer from Agilent) to measure the IgG concentration in the eluate at 280nm. After IgG binding, measure the IgG content in each of the supernatant, wash solution and eluate, and calculate the IgG content in each solution using the IgG calibration curve.
[0157] (3) Nonspecific adsorption rate when measuring SBC (%)
[0158] Based on 100% of the total IgG content (weight) of the supernatant, washing liquid and eluate determined in the above items 2) to 6), the IgG content (%) determined in the washing liquid was substituted into the nonspecific adsorption rate (%) when measuring SBC.
[0159] 2. Epoxy content (μmol / g), hydrophilic functional group content (μmol / g) and nonspecific adsorption rate (%) of particles (base resin) after epoxy passivation.
[0160] (1) Epoxy passivation
[0161] 1) The base resin was injected into a 1-thioglycerol solution (0.5M 1-thioglycerol+0.1M sodium sulfate+0.1M EDTA (pH 8.5)) and allowed to react at 37° C. for 17 hours. For Comparative Example 1, ethanolamine was used instead of 1-thioglycerol.
[0162] 2) Use a method such as centrifugation to sediment the particles, then remove the supernatant. Wash three times with deionized water.
[0163] (2) Epoxy group content after epoxy passivation (μmol / g)
[0164] Epoxy-passivated particles, ie, particles surface-treated with 1-thioglycerol, were prepared by drying at room temperature, and the epoxy content of the particles surface-treated with 1-thioglycerol was measured in the same manner as described above.
[0165] (3) Content of hydrophilic functional groups (μmol / g)
[0166] The hydrophilic functional group content of the particles surface-treated with 1-thioglycerol is measured as shown in the following <Equation>.
[0167] <Equation>
[0168] Hydrophilic functional group content after 1-thioglycerol surface treatment
[0169] =(epoxy content of particles before 1-thioglycerol surface treatment)×(number of hydroxyl functional groups in 1-thioglycerol)
[0170] (4) Nonspecific adsorption rate (%)
[0171] The epoxy-passivated particles were dried. The particles were then mixed with a 10 mg / mL solution of BSA (sigma A9418) dissolved in deionized water at a concentration of 31.3 mg / mL. The mixed solution was then stirred at room temperature for 18 hours, washed five times in deionized water, and dried at room temperature. The nonspecific adsorption rate was calculated by the ratio of the amount of BSA adsorbed to the particles relative to the total amount of BSA added during stirring at room temperature. At this time, the Pierce TM The amount of BSA adsorbed on the particles was analyzed using a BCA protein assay kit (Thermo Fischer).
[0172] [Table 7]
[0173] Evaluation of the Particles (Base Resin) of the Examples after Epoxy Passivation
[0174]
[0175]
[0176] [Table 8]
[0177] Evaluation of the Pellets (Base Resin) of Comparative Example after Epoxy Passivation
[0178]
[0179] ※In the case of Comparative Example 2, since the nonspecific adsorption rate of the base resin itself was determined to be a high value, the subsequent repeated nonspecific adsorption rate test (ie, the relevant experiment after the epoxy passivation treatment) was not performed.
[0180] ※ In Comparative Example 4, which has a significantly low epoxy content in the base resin itself, the nonspecific adsorption rate test for the base resin was not performed. In the same sense, the base resins of Comparative Examples 5 to 7 were not tested for nonspecific adsorption rates.
Claims
1. A method for preparing porous particles, the method comprising: The continuous phase composition (A) is mixed with the dispersed phase composition (B) comprising an epoxy-containing polymerizable monomer (b1), a crosslinking agent (b2) and a pore former (b3), and then the mixture is subjected to a suspension polymerization reaction to prepare a suspension polymerization product comprising units derived from the polymerizable monomer (b1) and the crosslinking agent (b2), wherein the dispersed phase composition comprises 50 parts by weight or more of the epoxy-containing polymerizable monomer (b1) based on 100 parts by weight of the crosslinking agent (b2), and The porogen (b3) includes a porogen having a Hansen solubility parameter difference with the epoxy-containing polymerizable monomer (b1) that satisfies a range of 1.30 to 4.
70.
2. The method for preparing porous particles according to claim 1, wherein: The dispersed phase composition includes 150 parts by weight or more of the epoxy-containing polymerizable monomer (b1) based on 100 parts by weight of the crosslinking agent (b2).
3. The method for preparing porous particles according to claim 1, wherein: The porogen (b3) includes a porogen having a Hansen solubility parameter difference of 2.50 to 4.50 from the epoxy-containing polymerizable monomer (b1).
4. The method for preparing porous particles according to claim 1, wherein: The pore former (b3) includes an acetate-based pore former.
5. The method for preparing porous particles according to claim 1, wherein: The dispersed phase composition includes 45 wt% or more of the pore former (b3) based on 100 wt% of the total content of the epoxy-containing polymerizable monomer (b1), the crosslinking agent (b2) and the pore former (b3).
6. The method for preparing porous particles according to claim 1, wherein: The crosslinking agent (b2) includes a crosslinking agent that does not contain a hydroxyl group (-OH), or is a crosslinking agent that does not contain a hydroxyl group (-OH).
7. The method for preparing porous particles according to claim 1, wherein: The continuous phase composition comprises water and a polymeric surfactant.
8. The method for preparing porous particles according to claim 1, wherein: The suspension polymerization product has a particle shape, and The particle D 50 Size ranges from 30μm to 70μm, (Among them, D 50 It means the particle size corresponding to 50% cumulative volume in the particle size distribution).
9. The method for preparing porous particles according to claim 1, wherein: The suspension polymerization product has a particle shape, and The particles have a pore size in the range of 30 nm to 500 nm as measured by mercury porosimetry, and a particle average surface pore size in the range of 110 nm to 240 nm, the particle average surface pore size being the arithmetic mean of the sizes of 20 or more pores observed on the particle surface.
10. The method for preparing porous particles according to claim 1, wherein: The suspension polymerization product has a particle shape, and The porosity of the particles is in the range of 15% to 40%.
11. The method for preparing porous particles according to claim 1, It also includes making the surface of the suspension polymerization product hydrophilic by passivation of epoxy groups.
12. The method for preparing porous particles according to claim 11, wherein: The suspension polymerization product has epoxy groups derived from the epoxy-containing polymerizable monomer (b1), and An epoxy deactivator having an epoxy reactive group and a hydrophilic group different from the epoxy reactive group is reacted with the suspension polymerization product having an epoxy group to make the surface of the suspension polymerization product hydrophilic.
13. The method for preparing porous particles according to claim 12, wherein: The epoxy passivating agent includes at least one of a thiol group and an amine group as the epoxy reactive group, and includes a hydroxyl group as a hydrophilic group different from the epoxy group.
14. A porous particle comprising polymerized units derived from a polymerizable monomer having an epoxy group and a crosslinking agent, The particles satisfy the following characteristics: The particle size (D) ranges from 30 μm to 70 μm. 50 ), Pore sizes in the range of 30 nm to 500 nm as measured by mercury porosimetry, a particle average surface pore size in the range of 110 nm to 240 nm, the particle average surface pore size being the arithmetic mean of the sizes of 20 or more pores observed on the particle surface, and Porosity in the range of 15% to 40%.
15. The porous particle according to claim 14, wherein: The porous particles are surface-treated with an epoxy passivating agent having an epoxy reactive group and a hydrophilic group different from the epoxy reactive group.
Citation Information
Patent Citations
Interlocking function control system and method using tire condition estimation
KR1020230013569A
Fin tube inspection device of heat recovery steam generator
KR1020230061331A